Examining the Role of Augmented Reality Interactivity on Student Performance: Mediating Effects of Visuospatial and Auditory Knowledge - Wahyuni, Dessy Seri; Koehler, Thomas; Saari, Erni Marlina; Sindu, I Gede Partha (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2025)
Augmented Reality (AR) has been widely used to support collaborative learning and provide students with facilities to complete tasks during the learning process. This study examines the impact of Augmented Reality on the interactivity, including controllability, responsiveness, and playfulness, of student performance through visuospatial and auditory Knowledge concerning Cognitive Load Theory (CLT). These elements must be processed simultaneously (both visually and audibly), resulting in a higher cognitive load. The CLT posits that learning is optimized when intrinsic, extraneous, and germane cognitive loads are balanced. This study employs the PLS-SEM approach to examine the conceptual model, as completed by 94 students in a vocational high school in Gianyar Regency who filled out the questionnaire. The findings of this study are novel, with visuospatial and auditory Knowledge that mediates AR interactivity on student performance in vocational high schools in Bali. These two forms of knowledge act as cognitive bridges, combining visuospatial and auditory knowledge between interactivity and achievement. When these modalities are well-integrated, they distribute cognitive load across channels (dual-channel processing), enhancing student performance. Antecedents of perceived AR interactivity, such as controllability and responsiveness, have a more significant influence on the mediator variables than playfulness, which enhances and enhances students’ achievement in vocational high schools. Visuospatial Knowledge helps learners mentally simulate spatial relationships, which is crucial in tasks like shaping ring components, whereas auditory Knowledge supports sequencing and procedural memory. The interactivity of AR can boost engagement and motivation, which translates into enhanced student performance, especially in vocational tasks like crafting a ring, which require precision, tactile feedback, and procedural mastery.